2012
DOI: 10.1016/j.bbmt.2011.12.579
|View full text |Cite
|
Sign up to set email alerts
|

Early Human Herpesvirus Type 6 Reactivation after Allogeneic Stem Cell Transplantation: A Large-Scale Clinical Study

Abstract: This study investigated the impact of human herpesvirus type 6 (HHV6) reactivation within 100 days of allogeneic stem cell transplantation (allo-SCT) on patient outcomes. HHV6 plasma loads were monitored weekly by quantitative PCR. Of 235 consecutive patients, 112 (48%) had an early positive HHV6 PCR test (group A) and 123 (52%) did not (group B). HHV6 reactivation was less frequent in patients who received reduced-intensity conditioning (P = .028). In group A, only 6 patients (5%) were asymptomatic; the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
108
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 48 publications
10
108
2
2
Order By: Relevance
“…HHV6 reactivation occurred early and before the occurrence of aGVHD, and thus before the initiation of immunosuppressive treatment, whereas the majority of EBV and HCMV reactivations (63%) occurred during aGVHD treatment (median interval for GVHD and EBV/HCMV reactivation 9 days, range 0-38, data not shown). Very recently, Dulery et al 6 confirmed these data and observed frequent HHV6 reactivation after MA conditioning prior to aGVHD treatment.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…HHV6 reactivation occurred early and before the occurrence of aGVHD, and thus before the initiation of immunosuppressive treatment, whereas the majority of EBV and HCMV reactivations (63%) occurred during aGVHD treatment (median interval for GVHD and EBV/HCMV reactivation 9 days, range 0-38, data not shown). Very recently, Dulery et al 6 confirmed these data and observed frequent HHV6 reactivation after MA conditioning prior to aGVHD treatment.…”
Section: Resultsmentioning
confidence: 73%
“…4 Very recently, Dulery et al 6 showed high incidence of HHV6 reactivation in adults after (MA) HSCT (48%). Others noted higher incidences of HHV6 reactivation: Zerr et al 7 performed a prospective study among 110 adult patients treated with HSCT, in which 47% of the patients had a HHV6 reactivation, 5 and Hentrich et al 25 found that 42% of 228 patients showed HHV6 reactivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some publications have suggested that the increased prevalence of HHV-6 reactivation may be due to the large number of immature ('antigen-naive') T cells present in umbilical CB, which inherently lacks the mature ('antigenexperienced' or 'memory') T cells necessary for immune reconstitution following HSCT. [35][36][37] In addition, because the newborn is generally naive for HHV-6 infection, CB lacks HHV-6-specific T cells, which could help in the containment of HHV-6 replication following engraftment. In fact, CB-derived T lymphocytes are often utilized to facilitate the active replication of HHV-6 in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 To date, however, HHV6-associated pleurisy has not been recognized as a complication of HSCT. In this report, we describe an adult HSCT recipient who developed HHV6-associated pleurisy after an unrelated cord blood transplantation (CBT).…”
Section: Hhv6mentioning
confidence: 99%